Inventory and Identification of Pathogens, Nematodes, and Entomopathogens Associated with Maize (Zea mays L.) in Rejang Lebong Regency, Bengkulu Province - Yenny Sariasih; Sempurna Ginting; Djamilah; Mimi Sutrawati; Ria Dwi Putri Anggrea Nengsih; Fiqri Ardiansyah; Putri Anisa (SINTA Journal (Science, Technology, and Agricultural), 2026)
Maize (Zea mays L.) is a strategic crop whose productivity is significantly affected by diseases caused by various plant pathogens. This study aimed to inventory and identify pathogens, nematodes, and entomopathogenic fungi associated with maize based on field symptoms, morphological characteristics, and molecular identification, specifically for the fungal pathogens detected. The research was conducted in major maize-producing areas of Rejang Lebong Regency, Bengkulu Province, Indonesia, located at an altitude of 700–900 m above sea level. Samples consisting of leaves, roots, and rhizosphere soil were collected from several maize fields. Field symptoms were observed, followed by pathogen isolation and morphological identification. Entomopathogenic fungi were cultured and purified on Sabouraud Dextrose Agar supplemented with Yeast Extract (SDAY) medium, while soil samples were processed using a modified sieving technique to extract nematodes. The results revealed four major diseases affecting maize, namely downy mildew, common rust, northern leaf blight, and leaf spot, caused by Peronosclerospora maydis, Puccinia sorghi, Exserohilum turcicum, and Cercospora sp., respectively. Six genera of plant-parasitic nematodes were identified, including Meloidogyne sp., Pratylenchus sp., Helicotylenchus sp., Rotylenchus sp., Tylenchus sp., and Nacobbus aberrans, all associated with root damage. Only one species of entomopathogenic fungus, Nomuraea rileyi, was isolated, indicating its potential as a biological control agent against insect pests. This study provides baseline information on the diversity of pests and pathogens associated with maize in Rejang Lebong Regency, which is essential for supporting integrated and sustainable pest and disease management.